E-Canteen Universitas Al Washliyah Labuhanbatu Berbasis WEB - Selamat Subagio; Samsir; Muhammad Rusdi (CSRID (Computer Science Research and Its Development Journal), 2026)
The rapid advancement of information technology has driven significant changes across various sectors, including facility management within higher education institutions. The Universitas Al Washliyah Labuhanbatu canteen—a crucial facility supporting daily campus activities—frequently faces operational challenges. These issues include long customer queues during break times, a lack of transparency in financial record-keeping, and difficulties for canteen owners in monitoring real-time stock levels. To address these problems, this study aimed to design and implement a web-based e-canteen management system. The system was designed to integrate the functional needs of students and lecturers (as buyers), canteen owners (as sellers), and campus administrators. The development process adopted the System Development Life Cycle (SDLC) methodology, encompassing user requirements analysis, database modeling (using ERD and DFD), and coding utilizing HTML, CSS, PHP, and MySQL technologies. Functionality testing demonstrated that the e-canteen application successfully reduces customer waiting times through an online ordering feature, provides clear digital cash flow records for management, and minimizes errors in product inventory tracking. The implementation of this platform is expected to accelerate digital transformation and help realize the "smart campus" concept at Universitas Al Washliyah Labuhanbatu.